Literature Review: Analysis of Saponins in Several Plants by HPLC Method and Its Utilization in Pharmaceutical Products - Prasasty, Vony Intan (Journal La Medihealtico, 2024)
This research aims to determine the content of saponin compounds found in several types of plants and their benefits for health. This research uses computer equipment and the Google Scholar database, Research Gate, NJC journal, Science Direct. The type of research used is an article review using data sources directly collected by the researcher. The data search was carried out through a Google Scholar database, using the keywords "saponin levels and HPLC". The screening results that met the requirements were used as references for 25 articles. This research used plant samples using the dried leaves of the plant and then extracted using the ultrasonication method, then using centrifugation to obtain a clear solution. The saponin analysis of the samples was carried out. Using HPLC with various columns. From these results, the saponin compound was shown to appear at a retention time of 53.09 minutes with an avarage saponin amount of 1.05%. Pharmacological studies show that saponins have many important such as enhancing immunity, antitumor, anti-inflammatory, antifungal, and anti-viral actions, reducing blood glucose and lipids, antioxidants, improving cardiovascular function. From the results of research conducted by several researchers above, it can be concluded that saponin analysis in several plants can be carried out using HPLC with a wavelength of 205nm. Saponin compounds as secondary metabolites have many benefits in the pharmaceutical field, including anti-inflammatory, hepatoprotective activity, immunological improvement, anti-tumor, anti-aging, treatment of cerebral edema, lung injury, myocardial ischemia reperfusion injury and gastric ulcers.